(untitled) (Research, Society and Development, 2022)
Introduction: the virus known as responsible for a worldwide pandemic, has the ability to infect several cell types, usually related to respiratory infections. Objective: to analyze the relationship of neurological disorders in patients diagnosed with Covid-19. Methodology: this is a retrospective, exploratory study and progressive information collection, with the exposure factors that followed the evolution of individuals infected by Covid-19. The sample consisted of 100 medical records of hospitalized patients with a positive diagnosis for Covid-19 and who had neurological disorders. Results: the main neurological disorders caused by Covid-19 were vomiting, headache, nausea, change in stimuli, change in the level of consciousness, dizziness, chills, convulsion, stroke, tremors and syncope. Final Considerations: according to the results of this study, the neurological disorders developed in patients diagnosed with Covid-19 are significant, which confirms the objectives of the present research, concluding that neurological disorders are really related to Covid-19 infection. 19, although most participants had the disease in a moderate or severe form. Keywords: Neurological manifestations; Covid-19; Respiratory infections; Nervous system.